Enhancing Early Childhood Teacher Pedagogical Competence Through STEAM-Based Instructional Training: An Experimental Study - Nur Fatwikiningsih; Nadiah Ismaeil (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
This study aims to ascertain the effects of STEAM-based instructional training on the pedagogical competencies of early childhood education teachers. The pedagogical competencies of early childhood education teachers in this study include knowledge teacher about consepts STEAM learning and performance teaching in developing teaching modules of STEAM include lesson planning and creating learning media. This research used experimental method. Design experiment used the one group pretest posttest with a sample of 112 members of IGTKI Jember. The training methods were lectures, discussions, simulations, and assignment projects. The training was conducted in the hall of the Education Office of Jember for duration of 12 hours. Data were collected through the cognitive tests about concepts STEAM learning and performance tests about developing ideas of STEAM learning. Data quantitative were analyzed used the Wilcoxon Signed-Rank test and data qualitative were used descriptive analyzed. The results found that training of the STEAM learning model had a significant effect on increased teachers knowledge and skills in STEAM learning with a significance level of 0,000, which is lower than 0,05. The indicators used to assess participantÔÇÖs satisfaction in this training include the training theme, punctuality, material completeness, content mastery, training method, interaction with trainee, and the trainerÔÇÖs attitude. The result found rata 98,5% trainee was satisfied. The observation found that trainee were able to develop STEAM ideas and creating learning media by utilizing materials available in the surrounding environment, and trainee were able to teaching STEAM with the four stages from explore, extend, engage, and evaluate.┬á